INDUCING INTRINSIC γ-RAY EMISSION OF THE INTERSTELLAR MEDIUM BY INTENSE FLUXES OF PROTONS AND α-PARTICLES IN ACTIVE GALACTIC NUCLEI - Doikov, D. N. (Одеські астрономічні публікації, 2020)
Cosmic-ray induced γ-ray emission in active galactic nuclei (AGN) has been examined in this study for the first time. Cross-sections for the formation of γ-quanta in such cosmic-ray collisions were selected in the 1-150 MeV energy range. Synthetic γ-ray spectra were computed for both interstellar gas and dust. At the same energies of particle collisions and induced emission of γ- quanta, energy intervals of diagnostic interest were determined. Specific characteristics of emission were detected in the energy ranges of 5-15 MeV and 23-30 MeV for most investigated elements. Diffuse continuous γ-ray spectra for the other energy ranges were less informative with regard to the determination of the chemical composition of interstellar gas. It has been shown that exploring cosmic-ray fluxes in the vicinity of galactic centres by employing the examined γ-ray spectra yields a pattern of their energy distribution. Diagrams of cross- sections for γ-quanta formation were computed for the α- process elements. Synthetic γ-ray spectra of interstellar gas and dust were calculated individually and collectively. It has been indicated that, under certain conditions in AGN, cross-sections for ionisation of atoms due to energy losses by cosmic-ray induced ionisation and γ-quanta emission resulting from collisions with cosmic rays are similar. It has been found that when the maximum of proton and α- particle energy distribution function falls within the investigated range of energies, it leads to the formation of the peak flux of γ-rays. This is particularly important for the interpretation of observations in the energy ranges of 5- 15 MeV and 23-30 MeV. Synthetic induced γ-ray spectra of interstellar dust were computed, and methods of their observations for silicate and carbon-containing dust, which account for 80% and 20% of the interstellar-dust total mass, respectively, were determined. It has been deduced that the contribution of Compton processes to γ-quanta emission can be neglected at the investigated energies.